Full‐Color Emission Polymer Carbon Dots with Quench‐Resistant Solid‐State Fluorescence. Issue 12 (28th September 2017) - Shao, Jieren; Zhu, Shoujun; Liu, Huiwen; Song, Yubin; Tao, Songyuan; Yang, Bai
Abstract: Polymer carbon dots (PCDs) represent a new class of carbon dots (CDs) possessing sub‐fluorophores and unique polymer‐like structures. However, like small molecule dyes and traditional CDs, PCDs often suffer from self‐quenching effect in solid state, limiting their potential applications. Moreover, it is hard to prepare PCDs that have the same chemical structure, exhibiting full‐color emission under one fixed excitation wavelength by only modulating the concentration of the PCDs. Herein, self‐quenching‐resistant solid‐state fluorescent polymer carbon dots (SSFPCDs) are prepared, which exhibit strong red SSF without any other additional solid matrices, while having a large production yield (≈89%) and a considerable quantum yield of 8.50%. When dispersed in water or solid matrices in gradient concentrations, they can exhibit yellow, green, and blue fluorescence, realizing the first SSFPCDs with the same chemical structure emitting in full‐color range by changing the ratio of SSFPCDs to the solid matrices. Abstract : A new type of polymer carbon dots (PCDs), with red quench‐resistant solid state fluorescence, is developed, providing a new way to achieve solid emission in the field of carbon dots. These PCDs also exhibit fullcolor concentration‐dependent emission, contributing to the realization of efficient full‐color solid state fluorescence.